2018
DOI: 10.1016/j.mineng.2018.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lab and pilot scale electric-pulse fragmentation systems for the recycling of ultra-high performance fibre-reinforced concrete

Abstract: Ultra-High Performance Fibre-Reinforced Concrete (UHPFRC) such as LafargeHolcim Ductal® is a new concrete product that incorporates large amounts of fine metal fibres, and is designed to have multiple advantages over traditional concrete products. These fibres, while providing additional strength, represent a new recycling challenge as they may block or increase wear of conventional mechanical apparatus, or be broken during processing rendering them unusable. High voltage electric-pulse fragmentation (EPF) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Above 9 kWh/t, the rate of size reduction decreases before levelling off in the high energy range (>15 kWh/t). Similar trends were reported in van der Wielen et al 2013, Zuo et al (2015) and Bru et al (2018), with the additional observation of an initial phase at low energy levels (<3 kWh/t) where little size reduction occurred. This initial phase was explained by the requirement of a material-specific threshold discharged energy to fully overcome particle strength and lead to the breakage of the majority of the particles (van der Wielen, 2013).…”
Section: Effect Of the Epf Discharged Energy On Electrical Comminutiosupporting
confidence: 88%
See 1 more Smart Citation
“…Above 9 kWh/t, the rate of size reduction decreases before levelling off in the high energy range (>15 kWh/t). Similar trends were reported in van der Wielen et al 2013, Zuo et al (2015) and Bru et al (2018), with the additional observation of an initial phase at low energy levels (<3 kWh/t) where little size reduction occurred. This initial phase was explained by the requirement of a material-specific threshold discharged energy to fully overcome particle strength and lead to the breakage of the majority of the particles (van der Wielen, 2013).…”
Section: Effect Of the Epf Discharged Energy On Electrical Comminutiosupporting
confidence: 88%
“…The operating parameters that can be changed are the voltage, electrode gap, pulse repetition rate and number of electric pulses applied to the sample. More details about the SELFRAG Lab can be found in Bru et al (2018) and van der Wielen (2013). In particular regarding the energy delivery of the lab system, two types of energy can be considered:…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Increasing the discharged energy input from 6.5 to 12.5 kWh/t led to a reduction in product size (Test 2), however overall product size reduction was not linearly correlated with energy input: multiplying the energy input by a factor 1.9 (from 6.5 to 12.5 kWh/t) only led to a reduction in P80 by a factor 1.4 (from 15.0 to 11.0 mm). This is due to the non-linear relationship between energy input and size reduction as already observed by several authors (van der Wielen et al, 2013;Zuo et al, 2015;Bru et al, 2018). Fig.…”
Section: Characterization Of the Products Obtained After The Two Epf mentioning
confidence: 61%
“…taking into account the energy used for the first fragmentation step (either with conventional or with the EPF method), is given in Table 4 with the energy consumption of the jaw crushing steps implemented in the conventional pathway instead of the EPF treatment estimated using the Bond formula law and the crushability index of the ore. Table 4 shows that using an EPF treatment in the comminution circuit leads to an increase of the overall comminution energy compared to the conventional route. This comparison should be considered carefully, however, since the discharged energy value of 6.5 kWh/t was chosen based on previous tests performed at labscale, and it was shown that the energy consumption of a batch lab-scale EPF equipment exceeds the one of a continuous pilot-scale [Instruction: EDF should be replaced here by "EPF" (typo mistake)]EDF system for similar performances ( Bru et al, 2018 ). It could therefore be possible that an EPF treatment performed at a discharged energy lower than 6.5 kWh/t still induces a marked weakening of the sample leading to a lower energy consumption of the whole comminution circuit.…”
Section: Table Footnotesmentioning
confidence: 99%
See 1 more Smart Citation